Raman spectroscopic signature of fractionalized excitations in the harmonic-honeycomb iridates β- and γ-Li2IrO3 - A. Glamazda; P. Lemmens; S. -H. Do; Y. S. Choi; K. -Y. Choi (Nature Communications, 2016)
Fractional excitations in quantum spin systems lead to exotic particles predicted in theory but difficult to observe in experiments. Here, Glamazda et al. report the dynamical Raman response of β- and γ-Li2IrO3is dominated by thermal damping of fermionic excitations, suggesting the emergence of Majorana fermions from spin fractionalization.